2017
DOI: 10.1002/ecm.1279
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation of soil microbial processes in tropical forests

Abstract: Abstract. Soil fungi and bacteria are the key players in the transformation and processing of carbon and nutrients in terrestrial ecosystems, yet controls on their abundance and activity are not well understood. Based on stoichiometric principles, soil microbial processes are expected to be limited by mineral nutrients, which are particularly scarce in often highly weathered tropical forest soils. Such limitation is directly relevant for the fate of soil carbon and global element cycles, but its extent and nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
207
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(237 citation statements)
references
References 207 publications
(491 reference statements)
23
207
4
3
Order By: Relevance
“…This might explain why microbes tend to respond negatively to N addition in lowland tropical forests (Camenzind et al. ) while plants tend to respond positively (this study). Unicellular microbes are probably more susceptible to the negative effects of soil acidification than are suberized roots.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This might explain why microbes tend to respond negatively to N addition in lowland tropical forests (Camenzind et al. ) while plants tend to respond positively (this study). Unicellular microbes are probably more susceptible to the negative effects of soil acidification than are suberized roots.…”
Section: Discussionmentioning
confidence: 64%
“…Camenzind et al. () recently did so for microbial responses to nutrient addition experiments (henceforth fertilization experiments). In lowland forests, microbes responded positively to P addition but not to N addition.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bio‐availability of nutrients (e.g. the percentage of nutrients that are actively assimilated into plants parts or microbial cells) after fertilizer treatments is sometimes very low (<20%); thus, endophytes may be unable to uptake nutrients in leaves following soil fertilization (Raun & Johnson, ; Zhang et al, ; Mohammadi, ; Willey, Sherwood, & Woolverton, ; but cf Camenzing, Hattenschwiler, Tresender, Lehmann, & Rillig, ). Thus, our results suggest the leaf tissue concentration of macronutrients is not the key in regulating the structure of bacterial endophyte communities, at least during the early seedling and sapling phase.…”
Section: Discussionmentioning
confidence: 99%
“…) and a recent meta‐analysis by Camenzind et al. () indicated that microbial limitation of P is widespread in tropical forests. In agreement, Turner and Wright () reported a significant increase in total microbial carbon (13%), N (21%) and P (49%) and a concurrent decrease in phosphatase activity (by 65%) with the addition of P but not N nor K at our site.…”
mentioning
confidence: 97%
“…Recent meta‐analyses reported that N addition has negative effects on soil microbial biomass and respiration in lowland tropical forests (Camenzind et al. ) and also in temperate forests where the negative effects are typically stronger (Treseder ; Zhou et al. ).…”
mentioning
confidence: 99%